PENERAPAN MODEL PJBL BERBANTUAN E-LKPD POSTER DIGITAL PADA PELAJARAN IPS UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS IV SD - Karin Widya Ayuningtyas; Erni Suharini; Eko Handoyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Social Studies learning in elementary schools often faces obstacles in visualizing abstract materials such as cultural diversity, resulting in low student creativity and engagement. This study aims to analyze the effectivenesns of implementing the Project Based Learning (PjBL) model assisted by Digital Poster Electronic Student Worksheets (E-LKPD) in increasing student creativity. This study used a Mixed Method with a Sequential Explanatory design. The subjects were 27 fourth-grade students at SD Negeri Songgom 01. Data collection was carried out through learning achievement tests, poster product assessments, observations, and student response questionnaires. Data analysis techniques used the N-Gain test for quantitative data and descriptive analysis for qualitative data. The results showed a significant increase in student creativity, evidenced by an average N-Gain score of 0.63 in the medium category. Students were able to produce original and attractive digital poster products using the Canva application. In addition, students showed high enthusiasm and positive responses to the applied learning. It can be concluded that the PjBL model assisted by Digital Poster E-LKPD is effective in increasing student creativity and creating a joyful and meaningful learning atmosphere.